Angiomatoid fibrous histiocytoma: Clinicopathological spectrum of five cases, including EWSR1-CREB1 positive result in a single case - Bharat Rekhi; Shraddha Adamane; Kiran Ghodke; Saral Desai; Nirmala A Jambhekar (Wolters Kluwer Medknow Publications, 2016)
Background: Angiomatoid fibrous histiocytoma (AFH) is an unusual soft tissue tumor (STT), characterized by recurrences, but rarely metastasis. Later, certain molecular signatures have been identified underlying this tumor, which at times, is either underdiagnosed as a benign vascular tumor, or over diagnosed as a high-grade pleomorphic sarcoma, including a malignant fibrous histiocytoma. Materials and Methods: Over a 14-year-period, five diagnosed cases of AFH were analyzed. Results: Five tumors occurred in three males and two females, over a wide age-range (median = 21, mean = 30 years); mostly in the extremities (4) (80%). Microscopically, most tumors were circumscribed, comprising large, blood-filed spaces with surrounding histiocytic cells and a "cuff" of lymphoplasmacytic cells. Three tumors revealed solid growth pattern with polygonal to spindle cells, including myxoid matrix in one of these tumors. On molecular analysis, this tumor exhibited EWS-CREB transcript. Immunohistochemically, various tumors were positive for CD68 (n = 2/2), epithelial membrane antigen (n = 3/4), CD99/MIC2 (n = 2/3), and desmin (n = 1/4). All tumors were surgically excised. On follow-up (n = 2), a single patient, who underwent wide-excision was free-of-disease (24 months), while another patient had a recurrence 4 months post tumor excision. Conclusions: This forms as the first documented series on clinicopathological features of AFH, a rare STT, from our country. Significant clinicopathological features include younger age, extremities as commonest site and histopathological appearance of blood-filled spaces with surrounding "cuff" of histiocytic cells and lymphocytes. Tumors with unusual histopathological tumor patterns require molecular confirmation. Surgical resection remains the treatment mainstay.